2010
DOI: 10.1007/s10930-010-9271-3
|View full text |Cite
|
Sign up to set email alerts
|

Residue 544 in Domain III of the Bacillus thuringiensis Cry1Ac Toxin is Involved in Protein Structure Stability

Abstract: A unique residue W544 in the beta18-beta19 loop of the Bacillus thuringiensis Cry1Ac toxin has been implicated in its toxicity. In this study, the effects of mutations at this residue on protein stability during protease treatment, UV irradiation, and preservation were examined. Residue 544 of Cry1Ac was involved in maintaining structural stability, and substitution of a polar group at this position was unfavorable to protein stability. One mutant, W544F, produced larger crystals and was more stable. This muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…A similar observation was found at mutant T542N in loop β16-β17 within the conserved block 4 of Cry1Ac: the insecticidal activity was increased against S. exigua larvae [61]. Meanwhile, it was reported that residue Trp544 in Cry1Ac loop β18-β19 has an influence on maintaining toxin stability towards H. armigera [62]. Domain III exhibits not only similar functional role as domain II in receptor recognition and binding, but also insecticidal specificity and stability that could be considered as its unique feature.…”
Section: Cry Toxinssupporting
confidence: 61%
“…A similar observation was found at mutant T542N in loop β16-β17 within the conserved block 4 of Cry1Ac: the insecticidal activity was increased against S. exigua larvae [61]. Meanwhile, it was reported that residue Trp544 in Cry1Ac loop β18-β19 has an influence on maintaining toxin stability towards H. armigera [62]. Domain III exhibits not only similar functional role as domain II in receptor recognition and binding, but also insecticidal specificity and stability that could be considered as its unique feature.…”
Section: Cry Toxinssupporting
confidence: 61%
“…Although the mutant W544F showed no change in its toxicity, which remained the same, it showed greater stability compared with the ultraviolet (UV) radiation exposure than its parental protein. 37 Lucena et al also reported in 2014 the importance of β16-β17 regions. In this study, they made mutations in Cry1Ac , increasing the toxic activity in 1.4 times compared with Spodoptera exigua , where they conclude the implication of domain III in the aspects mentioned above.…”
Section: Resultsmentioning
confidence: 94%
“…However, in Cry8Ka5, the negative charge of glutamate (E538) in this region disrupts the interaction with D520 (Figure 7). In the loops of the three Domains, some residues have been characterized as important for Cry protein toxicity due to their involvement in the interaction with insect receptors [72,87,99,100]. Domain III is the smallest of the three Domains and has been reported to function as a receptor binding site for GPI-ALP, GPI-APN [41,65] and Gal-NAc [31].…”
Section: In Silico Analyses Of Cry and Mutant Toxins For The Contrmentioning
confidence: 99%